2014
DOI: 10.1590/0034-7167.2014670608
|View full text |Cite
|
Sign up to set email alerts
|

Nível de dependência e qualidade de vida da população idosa

Abstract: RESUMOA qualidade de vida (QV) nos idosos é determinada em grande parte pelo seu estado funcional e condições de saúde. Com o objectivo de avaliar o nível de QV, os factores que a influenciam e identificar o grau de dependência dos idosos foi realizado um estudo observacional transversal do tipo exploratório-descritivo, englobando 93 idosos. Na recolha de dados utilizouse o índice de Barthel e MOS-SF 36. Na identificação dos níveis de dependência os resultados indicam-nos que 40,0% são independentes e 18,0% sã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
0
11
0
10
Order By: Relevance
“…The study found a positive correlation between the degree of dependence, physical and functional capacity and the quality of life index [28].…”
Section: Discussionmentioning
confidence: 78%
“…The study found a positive correlation between the degree of dependence, physical and functional capacity and the quality of life index [28].…”
Section: Discussionmentioning
confidence: 78%
“…Given this relationship, actions that aim to promote the physical and emotional well-being of this group are necessary, through an incentive to perform activities of daily living, as well as changes in lifestyle and participation in social groups [30]. It is verified that the elderly that participate in social groups had an active aging and monitored, tending to have a better QOL.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with the elderly [30] found that unmarried or widowed elderly people with low education level had worse QOL than the others. These data may have influenced the overall score of this survey not to be higher, although they tend to have a good QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com o avanço da idade, ocorre um declínio na massa magra, responsável por uma perda significativa de força que ocasiona limitações na independência funcional e, consequentemente, na realização das atividades de vida diária (AVDs) 1 . Tais limitações acarretam, também, a redução de sua qualidade de vida 4 , visto que a capacidade de realizar as atividades comuns de vida diária sem necessidade de ajuda de outra pessoa mostra-se essencial para a manutenção da qualidade de vida 5 .…”
Section: Introductionunclassified